The Influence of Brand Image and Brand Experience on Customer Brand Loyalty - Hermansyur; Bunga Aditi; Hafizah; Prasetyono Hendriarto (Institute of Computer Science (IOCS), 2021)
This research aims to find the influence of brand image and brand experience on brand loyalty. This research population is all regular customers in Suans Bakery, Sampling techniques using nonprobability sampling with a total of 88 samples. The data is obtained by giving a statement in the form of a questionnaire directly to the respondent to obtain valid data. Based on the results of processing, it is known that brand image and brand experience have a positive and significant influence on brand loyalty either simultaneously or partially. Determination test results found the value of R square by 64.2% this means a variation of brand loyalty that can be explained by a variety of independent brand image and brand experience of 64.2%, while the rest (35.8%) explained by other factors or variables outside the model.